INTERCULTURAL COMMUNICATION IN MULTICULTURAL SOCIETY (A STUDY ON THE ADAPTATION OF JAVANESE ETHNIC MIGRANT COMMUNITIES IN MATARAM UDIK VILLAGE) - Made Dewi Purnami; Tina Kartika, Nina Yudha Aryanti, Anna Gustina Zainal (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
The Balinese ethnic community has undergone transmigration due to the eruption of Mount Agung. Transmigration was carried out to Lampung Province, specifically in Central Lampung. This study aims to understand "How is intercultural communication among the Balinese ethnic group in a multicultural society?" Given this phenomenon, the author employs a qualitative research method using the symbolic interactionism model to observe behaviors and interactions of individuals, discerned through symbols and their meanings. Data collection techniques include observation, in-depth interviews, and documentation. The research findings reveal an interconnected adaptation between the Balinese ethnic migrants and the indigenous Lampung ethnic group. Due to mutual respect and appreciation between the ethnic groups, both migrants and natives are able to practice their respective cultures. The Javanese ethnic community is still respected for their use of the Javanese language in this village. Therefore, the relationship between these two ethnic groups can proceed smoothly without significant obstacles as each group has accepted the other as they are.